1958
DOI: 10.1021/ja01557a616
|View full text |Cite
|
Sign up to set email alerts
|

Additions and Corrections: Deuterium-isotope Effects in the Autoxidation of Aralkyl Hydrocarbons. Mechanism of the Interaction of Peroxy Radicals.

Abstract: ADDITIONS AND CORRECTIONS 6699i.e., by 20%. To correct this error: seven lines below the Bo formula read Garom = +2.7 X in the second line from the bottom read +3.7 p.pm.; in the first full paragraph of col. 2, line 7, read "separated by about 1.2 A," The empirical adjustment made in col. 2 and corrected above considerably reduces the effect of the 20'3. . error on all further calculations. The rest of the calculations are affected only very slightly, and the conclusions not at al1.-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
225
2
13

Year Published

1989
1989
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(249 citation statements)
references
References 0 publications
9
225
2
13
Order By: Relevance
“…A previous investigation [31] reports high k 6 values even at 30°C for different substrates in which termination is due to secondary peroxyl radicals. According to Howard and Ingold [31], those substrate would terminate by disproproportionation [32] and the ease with which H is transferred plays a very important role in determining the rate constant for termination. Polyamide termination would thus display an interesting similarity with those reactions.…”
Section: Assessment Of Kinetic Parametersmentioning
confidence: 99%
“…A previous investigation [31] reports high k 6 values even at 30°C for different substrates in which termination is due to secondary peroxyl radicals. According to Howard and Ingold [31], those substrate would terminate by disproproportionation [32] and the ease with which H is transferred plays a very important role in determining the rate constant for termination. Polyamide termination would thus display an interesting similarity with those reactions.…”
Section: Assessment Of Kinetic Parametersmentioning
confidence: 99%
“…After purification of the BOOH, we found that the extent of damage to both pBR 322 and pUC 19 DNA induced by HRP (1.8 and 9.0 µM) was identical (within our experimental accuracy) to that induced by the same concentration of HRP + 60 mM pure BOOH (compare lanes 2 and 3 with lanes 7 and 8 in Figures 4 and 5) (for duplicate experiments, see Figures S7-S9 in the Supporting Information). Furthermore, even in such 'clean' systems 10 mM Trolox exerted little or no protective effect on the SC DNA (see Figures 4,5, and S7-S9). Damage to pUC 19 by 9 µM HRP and 60 mM pure BOOH was essentially the same for BOOH purified by azeotropic distillation and for that further purified by recrystallization from hexane (see Figure S12).…”
Section: Resultsmentioning
confidence: 99%
“…Parts of the observed DMPO-OH and DEPMPO-OH might be produced via other pathways. Koga et al reported (26) that 1 O 2 is formed during the Fe 3+ -catalyzed decomposition of LOOH, probably via the Russell mechanism (27). The formation of DMPO-OH during the reaction between DMPO and 1 O 2 has also been reported (10,11).…”
Section: Discussionmentioning
confidence: 96%